INTERPRETATIONS OF COMPLICATED FOLDED STRUCTURES AT THE LOWER PARTS OF ANTARCTIC AND GREENLAND ICE SHEETS - Alexey N. Markov; Pavel G. Тalalay; Dorthe Dahl-Jensen (Geography, Environment, Sustainability)
Complicated folded structures were recently recorded by radar survey in the lower portions of the Antarctic and Greenland ice sheets. From a geological point of view the Antarctic and Greenland ice sheets are considered as geological features, while the ice is classified as sedimentary or metamorphic rock. In this regard the genesis of the ice sheets is analyzed from the perspective of geodynamics and metamorphism, and complicated folded structures on radar profiles are interpreted as tectonic and metamorphic structures. This study considers the processes of three kinds of tectonic structures: glacial diapirs, glacial diapir folds and glacial intrusions. Radar profiles not only capture ice flow structure but can also detect the thermobaric field in ice sheet, and in this case the complicated folded structures are interpreted as representative of recorded metastable boundaries of ice recrystallization.